Autorzy:Aleksandra Ciszkowska, Alina Przychoda, Zygmunt Łaszczyk
Wydawnictwo:WSiP
Rok wydania:2012
Oblicz: a) -2*(-3)*(-11), b) 5*(-(-2)+(-3), c) -3*((-2+1)-4 4.2 gwiazdek na podstawie 5 opinii

Oblicz: a) -2*(-3)*(-11), b) 5*(-(-2)+(-3), c) -3*((-2+1)-4

14Zadanie
15Zadanie
16Zadanie
17Zadanie
18Zadanie
19Zadanie
20Zadanie
21Zadanie
22Zadanie

a)

`-2*(-3)*(-11)=-2*33=(-66)`

b)

`5*(-(-2)+(-3))= 5*(2+(-3))=5*(-1)=(-5)`

c)

`-3*((-2+1)-4)=-3*((-1)-4)=-3*(-5)=15`

d)

`-(-(6+(-7)))=-(-(-1)))=(-1)`

e)

`-(-5-(-3))=-(-5-(-3))=-(-5+3)=-(-2)=2`

f)

`-(-2)^3-(-2)^2=-(-8)-4=8-4=4`